Comparison of the Effectiveness of Cognitive–Behavioral Therapy and Short-Term Solution-Focused Therapy on Intolerance of Uncertainty in Pregnant Women - Irvani, Farnoosh; Bolghan-Abadi, Mustafa; Mansouri, Ahmad (Psychology of Woman Journal, 2026)
Objective: The purpose of the present study was to compare the effectiveness of cognitive–behavioral therapy (CBT) and short-term solution-focused therapy (SFBT) on intolerance of uncertainty among pregnant women in 2024. Methods and Materials: This study was applied in purpose and employed an experimental design with a pretest–posttest–follow-up structure and a control group. The statistical population consisted of all pregnant women who visited comprehensive health service centers and obstetric specialists in Semnan City and had become pregnant naturally or through assisted reproductive techniques in 2021 and 2022. A total of 66 pregnant women were selected through convenience sampling. Data were collected using standardized questionnaires and analyzed using SPSS software, version 27. To measure intolerance of uncertainty, the Freeston Intolerance of Uncertainty Scale was employed. Findings: The results indicated that both cognitive–behavioral therapy and short-term solution-focused therapy significantly reduced intolerance of uncertainty among pregnant women, demonstrating the effectiveness of both approaches. Statistically, the mean score of the short-term solution-focused group was lower than that of the cognitive–behavioral group, indicating a greater impact of this therapeutic method on intolerance of uncertainty. Conclusion: Based on the findings, it can be concluded that both therapeutic approaches were effective in reducing intolerance of uncertainty and maintained stable effectiveness over time. Therefore, it is recommended that behavioral therapy specialists incorporate the findings of this study into their treatment programs.